Bowel screening: a mini literature review - Khattabi, Marwa; Alsammak, Mai (International Journal Of Community Medicine And Public Health, 2024)
Bowel cancer is a global health issue with more than 500.000 yearly new cases and a 12.6% mortality of all cancer cases. Studies suggest the financial burden of bowel cancer in Europe in 2015 was estimated at 19.1 billion Euros. Effective bowel screening promotes prevention and early detection of bowel cancer. There is a variation in bowel screening uptake across the globe, trials and pilot studies in the UK suggest uptake is around 50-60% in the UK, compared to much lower uptake in lower income countries. This mini literature review aims to shed some light on the magnitude of the problem, global variations in screening uptake, barriers to bowel screening uptake and explore ways to improve bowel screening uptake. Personal beliefs, social taboo and lack of knowledge are some of the barriers identified in this review, healthcare professionals have a pivotal role in opportunistic health promotion and encouraging patients to utilize bowel screening services, furthermore health educational campaigns targeting school children, students and other groups in the wider community may help increase bowel cancer awareness and the importance of bowel screening. A national recall system for bowel screening is an important step in improving uptake in low-income countries who have not achieved such a service yet.